Realism, Form and the Postcolonial Novel - Robinette, N. author. aut Link
VIII, 79 p. 2 illus.
Keywords: Confronted with apartheid, dictatorship or the sheer scale of global economics, realism can no longer function with the certainties of the nineteenth century. Free Realist Style considers how the style of the realist novel changes as its epistemological horizons narrow.